PENERAPAN MODEL CTL BERBASIS PERMAINAN SASOR TERHADAP KEMAMPUAN BERHITUNG DAN MOTIVASI BELAJAR PESERTA DIDIK - Rudi Hartono (FKIP Universitas Cenderawasih, 2025)
Abstract: This study aims to analyze the effect of the Contextual Teaching and Learning (CTL) model integrated with the traditional sasor game on the arithmetic skills and learning motivation of students residing in remote, frontier, and outermost (3T) regions. The research employed a quantitative quasi-experimental approach with a Nonequivalent Control Group Design using a saturated sample of 54 third-grade students at SD Negeri 1 Obaa, Mappi Regency. Data were collected via achievement tests, questionnaires, and observation sheets, and subsequently analyzed using MANOVA, Normalized Gain (N-Gain), and Effect Size measurements. The MANOVA results indicated a significant simultaneous effect (p = 0.000) with the treatment contributing 62.3% to the variance. The experimental group demonstrated a highly effective improvement in arithmetic skills (N-Gain of 0.71) and superior final motivation scores (86.50) compared to the control group. This ethnomathematics integration is proven to create a concrete, adaptive, interactive, and conducive learning atmosphere for students in the hinterlands of South Papua. In conclusion, the sasor game-integrated CTL model is highly effective in sustainably boosting students' cognitive and affective performance. Keywords: Contextual Teaching and Learning (CTL); traditional sasor game; arithmetic skills; learning motivation; ethnomathematics. Abstrak: Penelitian ini bertujuan untuk menganalisis pengaruh model Contextual Teaching and Learning (CTL) berbasis permainan tradisional sasor terhadap kemampuan berhitung dan motivasi belajar peserta didik yang hidup di wilayah tertinggal 3T. Metode penelitian menggunakan pendekatan kuantitatif eksperimen semu dengan rancangan Nonequivalent Control Group Design terhadap sampel jenuh sebanyak 54 siswa kelas III SD Negeri 1 Obaa, Kabupaten Mappi. Data dikumpulkan melalui instrumen tes, angket, dan lembar observasi, lalu dianalisis menggunakan uji MANOVA, Normalized Gain (N-Gain), dan pengukuran Effect Size. Hasil uji MANOVA menunjukkan pengaruh simultan yang signifikan (p = 0,000) dengan kontribusi dampak perlakuan sebesar 62,3%. Kelompok eksperimen mencatatkan efektivitas peningkatan berhitung tinggi (N-Gain 0,71) serta skor akhir motivasi yang unggul (86,50) dibandingkan kelompok kontrol. Integrasi etnomatematika ini terbukti menciptakan atmosfer pembelajaran konkret, adaptif, interaktif, dan kondusif bagi siswa pedalaman Papua Selatan. Simpulannya, model CTL berbasis permainan sasor terbukti sangat efektif dalam mendongkrak performa kognitif sekaligus afektif siswa secara berkelanjutan. Kata Kunci: Contextual Teaching and Learning (CTL); permainan tradisional sasor; kemampuan berhitung; motivasi belajar; etnomatematika.